Cabergoline versus bromocriptine in the treatment of hyperprolactinemia: a systematic review of randomized controlled trials and meta-analysis - Nunes, Vânia dos Santos [UNESP]; El Dib, Regina [UNESP]; Boguszewski, Cesar Luiz; Nogueira, Célia Regina [UNESP] (Springer, 2011)
Cabergoline and bromocriptine are the most used drugs in the treatment of hyperprolactinemia, they are able to normalize the prolactin levels, restore gonadal function and promote tumor reduction in the majority of patients. We undertake a systematic review and meta-analysis of randomized controlled trials to compare cabergoline versus bromocriptine in the treatment of patients with idiopathic hyperprolactinemia and prolactinomas. The data sources were: Embase, Pubmed, Lilacs and Cochrane Central. The outcome measures were: normalization of prolactin secretion, restoration of gonadal function, reduction of tumoral volume, quality of life and adverse drug effects. Were identified 418 references and after screening by title and abstract, we obtained complete copies of 34 articles potentially eligible for inclusion in the review. From this total, 19 were selected to be included, but fifteen of them were excluded due to the following reasons: one randomized study compared cabergoline versus placebo and other randomized study compared different doses of cabergoline; five references were cases series; four were only controlled studies; three were retrospectives series and; one was a cohort study. Therefore, four publications were included in the review and in the final analysis. The meta-analysis of normalization of serum prolactin levels and menstruation with return of ovulatory cycle showed a significant difference in favor of cabergoline group (RR 0.67 [CI 95% 0.57, 0.80]) e (RR 0.74 [CI 95% 0.67, 0.83]), respectively. The number of adverse effects was significantly higher in the bromocriptine number than in cabergoline group (RR 1.43 [CI 95% 1.03, 1.98]). The meta-analysis showed new evidence favoring the use of cabergoline in comparison with bromocriptine for the treatment of prolactinomas and idiopathic hyperprolactinemia.
Keywords: Hyperprolactinemia; Prolactinoma; Systematic review; Meta-analysis; Dopaminergic agonists